Coral Li/Ca in micro-structural domains as a temperature proxy - MONTAGNA P; CORREA ML; RUGGEBERG A; MCCULLOCH M; RODOLFO METALPA R; DULLO WC; FERRIER PAGES C; FREIWALD A; HENDERSON GM; RUSSO S; SILENZI S; TAVIANI M.; et al. (2008)
Coral skeletons are valuable geochemical archives of environmental change, although coral physiology has to varying degrees imprinted a ‘vital effect’ complicating paleoclimate reconstructions. In order to decipher environmental from physiological effects we have utilised high sensitivity laser ablation ICPMS to examine Li/Ca variations in the aragonite theca of living specimens of shallow (C. caespitosa) and deep-water (L. pertusa) corals at different temperature depth regimes, together with samples cultured in temperaturecontrolled tanks. The Li/Ca variations at micron-resolution are large and correlated with centres of calcification versus fibrous aragonite. The Li/Ca composition of the fibrous aragonite however appears to be primarily controlled by water temperature with the distribution coefficients (DLi/Ca) of L. pertusa rapidly decreasing with increasing water temperature indicating a stronger sensitivity for Li/Ca at lower temperatures, whereas the DLi/Ca for C. caespitosa follows an exponential regression. The application of coral Li/Ca paleothermometry on specifically identified micro-structural domains thus offers a unique opportunity to reconstruct changes in water temperatures at different depths in the water column.